TRAFFIC CRIMES: ASPECTS BETWEEN INTENTIONAL AND GUILTY CRIME - Cabral de Albuquerque, Rafael (Revista Gênero e Interdisciplinaridade, 2024)
The topic of traffic crimes is a growing concern in many countries, including Brazil, due to serious accidents, injuries, and deaths resulting from violations of traffic laws. The aim of this work is to analyze the characteristics and main differences between intentional and negligent crimes, as well as their application to traffic offenses. The distinction between intentional and negligent crimes in traffic offenses lies in the presence or absence of intent, which is the deliberate and conscious will to commit the crime, according to current legislation. The classification of a traffic offense as intentional or negligent depends on a detailed analysis of the circumstances of each specific case, taking into account factors such as the conduct of the agent, the resulting outcome, the causal link, and the agent’s culpability, based on court precedents. The development of this work highlights that traffic offenses are classified in the Brazilian Traffic Code (CTB) and can be categorized as intentional or negligent, depending on the conduct of the agent and the resulting outcome. Intentional crimes occur when the driver acts with the intention of causing the outcome, while negligent crimes occur when the driver behaves negligently, recklessly, or in an unskilled manner, resulting in a traffic accident. The reference work used in this study emphasizes the importance of considering the presence or absence of intent in differentiating between intentional and negligent crimes in traffic offenses and underscores the need for an individualized analysis of each case. This research employed a bibliographic review methodology, which was essential to provide a theoretical foundation for the study and identify gaps and research opportunities on this topic. In conclusion, the application of intent or negligence to a specific case will depend on the evidence presented to the judge, both by the Public Prosecutor’s Office at the time of indictment and by the defense during the presentation of the response to the charges. Thus, the classification of the conduct ceases to be of an objective nature and becomes subjectively evaluated by the judge.